Ethics and moral philosophy - Brooks, Thom. (Studies in Moral Philosophy, 2011)
Ethics and moral philosophy is an area of particular interest today. This book brings together some of the most important essays in this area. The essays have all appeared recently in the Journal of Moral Philosophy , an internationally recognized leading philosophy journal. This book is divided into five sections: practical reason, particularism, moral realism, virtue ethics, and ethics and moral philosophy more generally.